PENINGKATAN PRESTASI BELAJAR MATEMATIKA MELALUI PEMBELAJARAN BEHAVIORISTIK PADA SISWA SMPN 1 KARANGPLOSO - Games Yunastutik (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2017)
This two cycle classroom research aims to improve student achievement in mathematics through behavioristic learning for students of class VII SMPN 1 Karangploso. In each cycle, the researcher applied: planning, acting, observing and reflection as the research procedure.  Data of this study were students’ interactions using behavior learning.  Data were analyzed using descriptive statistics.  The results showed that in the pre-cycle students’ mean score was 82. The mean score increased into 83 and 86 respectively in the cycle I and cycle II.  This means the achievement on mathematic lesson using the behavioristic is quite good as indicated that the attainment is  ≥ 75%.  In addition, students activities during the learning process also increased based on observations of the first cycle and the cycle two, admitting that behavioristic learning evidently improves accomplishment in mathematics for the seventh graders of SMPN 1 Karangploso.